Corneal ectasia after myopic laser in situ keratomileusis: a long-term study - Spadea L (Dove Medical Press, 2012)
Leopoldo Spadea,1 Emilia Cantera,2 Magdalena Cortes,2 Nicole Evangelista Conocchia,1 Charles WM Stewart11University of L’Aquila, Department of Biotechnological and Applied Clinical Sciences, Eye Clinic, L’Aquila, 2Villa Stuart Clinic, Department of Ophthalmic Sciences, Rome, ItalyBackground: The purpose of this study was to evaluate the long-term postoperative incidence of and key factors in the genesis of corneal ectasia after myopic laser-assisted in situ keratomileusis (LASIK) in a large number of cases.Methods: A retrospective review of one surgeon's myopic LASIK database was performed. Patients were stratified into two groups based on date of surgery, ie, group 1 (1313 eyes) from 1999 to 2001 and group 2 (2714 eyes) from 2001 to 2003. Visual acuity, refraction, pachymetry, and corneal topography data were available for each patient from examinations performed both before and after the refractive procedures.Results: Of the 4027 surgically treated eyes, 23 (0.57%) developed keratectasia during the follow-up period, which was a minimum seven years; nine eyes (0.69%) were from group 1 and 14 eyes (0.51%) were from group 2. The onset of corneal ectasia was at 2.57 ± 1.04 (range 1–4) years and 2.64 ± 1.29 (range 0.5–5) years, respectively, for groups 1 and 2. The most important preoperative risk factors using the Randleman Ectasia Risk Score System were manifest refractive spherical error in group 1 and a thin residual stromal bed in group 2. Each of the cases that developed corneal ectasia had risk factors that were identified.Conclusion: Ectasia was an uncommon outcome after an otherwise uncomplicated laser in situ keratomileusis procedure. The variables present in eyes developing postoperative LASIK ectasia can be better understood using the Randleman Ectasia Risk Score System.Keywords: corneal topography, Ectasia Risk Score System, keratectasia, myopia, LASIK